2019
DOI: 10.1136/bmjopen-2018-028076
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, experiences and barriers to lifestyle modifications in first-generation Middle Eastern immigrants to Sweden: a qualitative study

Abstract: ObjectiveThe prevalence of type 2 diabetes (T2D) among Iraqi immigrants to Sweden is high and partly related to sedentary physical activity and calorie dense food. The aim of the present study was to explore perceptions, experiences and barriers concerning lifestyle modifications (LSM) in Iraqi immigrants to Sweden at risk for T2D.DesignA qualitative thematic analysis was conducted on data collected from gender-specific focus group interviews which took place during a culturally adapted randomised controlled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 36 publications
(80 reference statements)
1
41
0
Order By: Relevance
“…Aged 20–59 years. Focus groups Thematic analysis Olaya-Contreras et al (2019) [ 35 ] Sweden To explore perceptions, experiences and barriers concerning lifestyle modifications in Iraqi immigrants to Sweden at risk for Type 2 Diabetes. Yes 33 Iraqi immigrants (19 women, 14 men).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aged 20–59 years. Focus groups Thematic analysis Olaya-Contreras et al (2019) [ 35 ] Sweden To explore perceptions, experiences and barriers concerning lifestyle modifications in Iraqi immigrants to Sweden at risk for Type 2 Diabetes. Yes 33 Iraqi immigrants (19 women, 14 men).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in Australia [ 29 , 30 , 36 , 41 , 43 ], three in the US [ 33 , 38 , 42 ], three in the Netherlands [ 34 , 37 , 44 ], three in Sweden [ 32 , 35 , 40 ], and one in Canada [ 39 ]. The target population of the 15 studies included Arab migrant groups from the Middle East and North Africa, with a total of five studies exclusively focusing on Arab migrant samples [ 29 , 33 , 35 , 38 , 42 ]. A total of six studies focused on physical activity as the primary behaviour of interest [ 29 , 30 , 32 , 38 , 40 , 43 ], while the remaining studies focused on physical activity in addition to other lifestyle behaviours (e.g., physical activity and diet).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 58 Those participants succeeding in changing lifestyles experienced positive support from their family relatives in their efforts. 60 In addition, the study showed beneficial effects on mental health. 61 …”
Section: Introductionmentioning
confidence: 87%